Deficiency of Endothelial CD40 Induces a Stable Plaque Phenotype and Limits Inflammatory Cell Recruitment to Atherosclerotic Lesions in Mice - Gissler, Mark Colin; Scherrer, Philipp; Anto-Michel, Nathaly; Pennig, Jan; Hoppe, Natalie; Füner, Lisa; Härdtner, Carmen; Stachon, Peter; Li, Xiaowei; Mitre, Lucia Sol; Marchini, Timoteo; Madl, Josef; Wadle, Carolin; Hilgendorf, Ingo; von zur Mühlen, Constantin; Bode, Christoph; Weber, Christian; Lutgens, Esther; Wolf, Dennis; Gerdes, Norbert; Zirlik, Andreas; Willecke, Florian (Thrombosis and Haemostasis, 2021)
Objectives The co-stimulatory CD40L–CD40 dyad exerts a critical role in atherosclerosis by modulating leukocyte accumulation into developing atherosclerotic plaques. The requirement for cell-type specific expression of both molecules, however, remains elusive. Here, we evaluate the contribution of CD40 expressed on endothelial cells (ECs) in a mouse model of atherosclerosis.Methods and Results Atherosclerotic plaques of apolipoprotein E-deficient (Apoe−/−) mice and humans displayed increased expression of CD40 on ECs compared with controls. To interrogate the role of CD40 on ECs in atherosclerosis, we induced EC-specific (BmxCreERT2-driven) deficiency of CD40 in Apoe−/− mice. After feeding a chow diet for 25 weeks, EC-specific deletion of CD40 (iEC-CD40) ameliorated plaque lipid deposition and lesional macrophage accumulation but increased intimal smooth muscle cell and collagen content, while atherosclerotic lesion size did not change. Leukocyte adhesion to the vessel wall was impaired in iEC-CD40-deficient mice as demonstrated by intravital microscopy. In accord, expression of vascular cell adhesion molecule 1 (VCAM-1) and intercellular adhesion molecule 1 (ICAM-1) in the vascular endothelium declined after deletion of CD40. In vitro, antibody-mediated inhibition of human endothelial CD40 significantly abated monocyte adhesion on ECs.Conclusion Endothelial deficiency of CD40 in mice promotes structural features associated with a stable plaque phenotype in humans and decreases leukocyte adhesion. These results suggest that endothelial-expressed CD40 contributes to inflammatory cell migration and consecutive plaque formation in atherogenesis.
Keywords: CD40; CD40L; atherosclerosis; inflammation; plaque phenotype